1998
DOI: 10.1038/sj.ejcn.1600518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psyllium on gastric emptying, hunger feeling and food intake in normal volunteers: a double blind study

Abstract: Objective: To assess whether psyllium, a soluble dietary ®bre, could, at an acceptable dose (7.4 g), delay gastric emptying of a low-calorie meal, and reduce hunger feeling and energy intake, without requiring intimate mixing with the meal. Design: A double blind randomized cross over study with 14 normal volunteers, to evaluate the effect of this dose of psyllium on postprandial serum glucose, triglycerides and insulin levels, and on gastric fullness, hunger feeling and food intake. Methods: Gastric emptying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 29 publications
3
55
0
10
Order By: Relevance
“…However, and in agreement with Fernández et al (1998), García et al (2000) and Rigaud et al (1998), we think that these changes principally occur because the fiber forms a highly viscous solution, trapping levodopa inside it, and therefore, there is a decrease in drug absorption in the intestine and consequently lower values for C max are obtained.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, and in agreement with Fernández et al (1998), García et al (2000) and Rigaud et al (1998), we think that these changes principally occur because the fiber forms a highly viscous solution, trapping levodopa inside it, and therefore, there is a decrease in drug absorption in the intestine and consequently lower values for C max are obtained.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, other authors did not find this action: Bianchi and Capurso (2002) demonstrated that the addition of different dietary fibers (guar gum and ispaghula) to a solid meal did not influence gastric emptying. Frost et al (2003) probed that psyllium-enriched pasta had no significant effect on gastric emptying and Rigaud et al (1998) concluded that psyllium did not slow down the gastric emptying of hydrosoluble nutrients, but increased the time allowed for intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…This last fact is important because, due to the relatively short duration of this study, fructosamine is a better marker than GhbA 1c . This reduction might be due to psyllium's ability to reduce hunger feelings and energy intake (Rigaud et al, 1998). We have no data available from other authors about how psyllium modifies these parameters.…”
Section: Discussionmentioning
confidence: 90%
“…Most notably, the results of many studies conducted on humans showed that psyllium reduces caloric consumption while improving satiety. [28][29][30] The action of psyllium on caloric intake and satiety could result from its capacity to increase chyme viscosity, which slows down gastric emptying, as shown previously in humans 28 and dogs. 31 To assess the relative effects of both fiber and protein supplementation most appropriately, 4 similarly formulated diets would have been needed, which only differed in fiber and protein content (eg, HPHF, HP only, HF only, and neither HP nor HF).…”
Section: Discussionmentioning
confidence: 99%